2021
DOI: 10.4103/endo.endo_103_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of root canal morphology of mandibular premolars using cone-beam computed tomography in Rajasthan subpopulation - A retrospective study

Abstract: Aim: The purpose of this study was to evaluate root canal morphology in mandibular first and second premolars among Rajasthan subpopulation in Jaipur city using cone-beam computed tomography (CBCT). Materials and Methods: CBCT scans of 740 fully erupted mandibular first and second premolars were taken and assessed by two endodontists. Inter-examiner reliability was determined. Results: The root canal morphology of 380 permanent mandibular fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Matherne et al [15] and Mittal et al [16] showed the superiority of axial images of CBCT over other diagnostic methods in locating additional canals. Thus, CBCT imaging is not only noninvasive but also a highly sensitive method for morphological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Matherne et al [15] and Mittal et al [16] showed the superiority of axial images of CBCT over other diagnostic methods in locating additional canals. Thus, CBCT imaging is not only noninvasive but also a highly sensitive method for morphological studies.…”
Section: Discussionmentioning
confidence: 99%